Traces of Dissent: The Journal Filmspiegel and Readership Responses to the Ban of Frank Beyer's DEFA Film Spur der Steine (1965/66). Issue 1 (2nd September 2020) - Wedel, Michael
Abstract : The 11th Plenum of the Central Committee of the East German SED, held in December 1965 and resulting in the ban of over a dozen feature films, marks the most ferocious act of political censorship in the history of the state-owned production company DEFA. The ideological agenda behind the decision-making process that led to the official branding of Spur der Steine ( Trace of Stones, 1965/66) is well documented, the critical acclaim of the forbidden films has steadily grown after their rediscovery in 1989. Still missing is any deeper insight into the reactions of the cinema-going public to this ruthless intervention of politics into GDR film culture. Based on recently discovered unpublished 'letters to the editor' of the journal Filmspiegel concerning the ban of Spur der Steine, this essay sets out to restore a crucial dimension to our understanding of the social reverberations of the 11th Plenum.